Evaluating the efficiency of some safe management methods for root-knot nematodes on eggplant in compare with a nematicide, Vaydate - Yousif, Hafiz Mohamed Dafalla; Al-Yahya, Fahad Abdullah; El-Qurashi, Mostafa Ahmed (Journal of agricultural, environmental and veterinary sciences, 2024)
Laboratory and greenhouse experiments were conducted for managing root-knot nematodes (RKNs) on eggplant using garlic extract and poultry manure compared with vaydate®.  Under laboratory conditions, garlic extract and poultry manure caused 99.5% and 77.5% mortality of second-stage juveniles (J2s) of root-knot nematodes (RKNs), respectively, compared to the vaydate® treatment (99.7-100%). Twelve treatments were designed and applied in greenhouse experiments to manage root-knot nematodes. Results showed that using garlic extract and poultry manure, either alone or combined with vaydate®, reduced the number of root galls and improved plant growth. The highest plant growth was observed with poultry manure treatment. Therefore, we concluded that eco-friendly biological control methods effectively managed RKNs and promoted plant growth.
Keywords: Root-knot nematodes; Vaydate; poultry manure; garlic extract; biocontrol